Exercise-dependent BDNF as a Modulatory Factor for the Executive Processing of Individuals in Course of Cognitive Decline. A Systematic Review - de Assis, Gilmara G.; Almondes, Katie Moraes de (Frontiers in Psychology, 2017)
Background: Aging naturally triggers a decline in cognition as result of deterioration in cerebral circuits, thus the executive functions (EFs) suffer changes that progress from mild to severe states of impairment. Exercise instead, works as a strategy for cognitive enhancement by modulating neuronal plasticity through the regulation of BDNF. However, whether the exercise-dependent BDNF may improve higher complexity processes such as the EFs is still in a studying process. Results: Current data on exercise-dependent BDNF changes for aging individuals in a course of cognitive impairment was summarized to investigate whether the exercise regulation of BDNF is effective to pronounce long term changes on executive controls. While the exercise-dependent regulation of BDNF is currently undeniable, the role of exercise dependent BDNF as a tool for the improvement of EFs in individuals with dementia is still less clear and seldom discussed. The summary of findings indicate a limited number of studies addressing exercise in order to discuss parameters related to either BDNF or executive functioning in such population conditions (n=215), further narrowing to a total of 5 studies presenting analysis of both parameters. Nonetheless, positive outcomes from BDNF and EF variables were displayed by all the populations exposed to exercise across studies. Aerobic exercise was shown to be a major source for the enhancement of the BDNF-dependent executive functioning, when compared to cognitive stimulation. Moreover, the effect of exercise-dependent BDNF on domains of executive functioning appears to occur in a dose-dependent manner for the aging individuals, independently of cognitive condition.